Satisfação do usuário com os serviços da atenção básica no Brasil: uma avaliação a partir da participação das equipes nos ciclos do PMAQ-AB - Protasio, Ane Polline Lacerda (2018)
The National Program for Access and Quality Improvement in Primary Care (PMAQ-AB) is carried out in periodic cycles and intends to achieve a national quality standard. This program aims to promote incremental changes in the Brazilian Primary Care (PC) practices per cycles and one of its objectives is to increase the service-orientation practices according to the needs and satisfaction level of Brazilian Primary Care users. In this context, this thesis presents as its main objective to obtain a decision support model based on the 2nd PMAQ-AB cycle, in order to conduct a comparative study between PC teams, which are participating since the 1st PMAQ-AB cycle (named here: group C12), and teams with their first evaluation just in the 2nd PMAQ-AB cycle (named here: group C2) by means of the identification of factors associated to users' satisfaction related to the offered care, the health care team and the health care facilities. In this way, it was performed a descriptive analysis and it was developed user satisfaction measurements to be the study outcomes as well as logistic regression was applied to obtain decision models to Brazil for each user satisfaction measurement including interactions between each variable presents in group C12 and group C2. As a result, it was observed that the majority of the users has been satisfied with the offered care, the health care team and the health care facilities. In addition, it was observed that some variables differ from group C12 to group C2 considering the user satisfaction: for satisfaction with the care team, the variables were the privacy in the doctor's office and to feel free to talk with the team about their worries; for satisfaction with the offered care, the variables were to feel respected by the health professionals, the distance to the PC health facility and its conditions; and for satisfaction with the health care facilities, the variables were the amount of chair in the PC health facility, use conditions and privacy into the doctor's office. In both groups, these conditions have had positive association with the user satisfaction, however with a greater chance in the C12 group related to C2 group. The ability of the care team to meet user needs, the bond with the health professionals, the work stability of the team, the appointment time and the care resolution also present positive association with the user satisfaction but to not differ between C12 group and C2 group. We conclude that the differences found between C12 group and C2 group could be attributed to the fact the teams from C12 group have already undergone enhancement during the two cycles and that it is possible to increase the user satisfaction level with just some changes in the PC practices since these changes are feasible to be put into action by managers and health professionals.